The The Influence of Social Media Marketing and E-Service Quality on Customer Loyalty in the Shopee Marketplace : A Case Study of the Subang District Community - Devy Widya Apriandi; Kuncorosidi Kuncorosidi; Shella Fransiska (JABI (Journal of Accounting and Business Issues), 2025)
The rapid growth of e-commerce in Indonesia has reshaped shopping behavior. Shopee remains the most-used marketplace, yet customer loyalty in areas like Subang District is still inconsistent. Price competition, similar promotions, and uneven digital services make users easily switch to other platforms. This study examines the effect of Social Media Marketing (SMM) and E-Service Quality (ESQ) on customer loyalty. SMM builds engagement through social media content, while ESQ emphasizes digital service quality such as speed, reliability, and security. A quantitative method was applied by distributing questionnaires to 70 Shopee users in Subang District and analyzing data using multiple linear regression. Findings reveal that both SMM and ESQ have a positive and significant influence on customer loyalty. Better social media strategies and service quality lead to stronger user commitment. The results highlight the importance of improving customer relationships and retention in regional e-commerce markets.